Entre classement et patrimonialisation : Les usages du patrimoine judéo-tunisien - Afef Mbarek (L’Année du Maghreb)
The Judeo-Tunisian heritage is currently undergoing a genuine reformulation. Its construction as such began as early as the colonial period, when manifestations of its recognition and protection were first observed. Among these manifestations are the classifications of the ancient necropolis of Gammarth and the Ghriba synagogue of Djerba as historical monuments. This article analyzes the cases of these two sites as well as that of the Great Synagogue of Tunis Hara, destroyed in 1960, in order to understand the the presence or absence of a heritagization processes. This work also attempts to study the roles that different actors (intra and extra-community, social and institutional) have played in the emergence of this component of Tunisian heritage.